HIBRIDITY OF THE CHACRACTERS IN MY SON THE FANATIC STORY BY HANIEF KURESHI - Michelle Intan Goh Rumengan Waworuntu; Tomi Arianto (BASIS (Bahasa dan Sastra Inggris), 2019)
This study aimed to reveal the forms of hybridity as a result of the existence of postcolonial cultural contact with the construction of a colonial form. Researchers revealed the hybridity represented by the characters Parvez and Ali in My Son the Fanatic Short Story by Hanief Kureshi. This study used the Postcolonialism approach in the hybridity concept of Homi K Bhabha. According to. Bhabha (1994) Hybridity is a cross between two different cultures in a tangent interaction. In this case, hybridity is not only seen as a fusion of culture but also cultural products placed in social and historical space under postcolonialism which are part of the imposition of colonial power relations. The qualitative descriptive method was used in this study because of its essence in descriptive text analysis in predetermined literary works. The results of this study indicated that there are two forms of hybridity representation in this study. First, the character of mimicry in the sense of ambiguity and contradictory character as a discourse of cultural devotion due to the colonial construction that was formed. Mimicry is represented by the character Parvez in the story. Second, the ambivalence represented by his son named Ali. Ali was aware of the colonial discriminatory against culture so he resisted the construction but on the other hand, he did not know what identity he should hold.